Telecommunication Industry Analysis in Algeria Using Porter’s Five Competitive Forces Model - Beldjazia, Omar; Boulahia, Tayeb; Echabli, Ferass (Finance and Business Economies Review, 2019)
This study aimed to analyze the competitive environment of telecommunication companies in Algeria by trying to apply the model of the five competitive forces of the Porter and dropping it on the telecommunications industry in Algeria, in addition to know the attractiveness of the industry in which it operates . The study reached a number of results: - The degree of pressure exerted by the five competitive forces, or the Porter model is different from that of the telecommunications sector in Algeria. The telecommunications companies (Mobilis, Djezzy, Ooredoo) are the most influential forces compared to processors and customers whose influence is weak in terms of their bargaining power. Indicates that there is no real threat to alternative products, while the threat to newcomers remains the only risk that may affect the competitiveness of the sector, but their entry remains subject to the state's decision. - The general environment of telecommunications companies in Algeria provides them with many opportunities to help them grow, their competitive environment is strategically attractive to their few competitors and the weakness of other competitive forces in the sector, which contributes to their profitability.